In the Virtual Extension. (Communications of the ACM, 2010)
Abstracts are presented for several articles published elsewhere in the issue, or available online at the ACM (Association for Computing Machinery) Digital Library, including "Thinkflickrthink: A Case Study on Strategic Tagging" by Eugenio Tisselli, "Plat_Forms: Is There One Best Web Development Technology?" by Lutz Prechelt, and "How a Service-Oriented Architecture May Change the Software Development Process" by Marc N. Haines and Marcus A. Rothenberger.